ANALISIS CELEBRITY ENDORSER, HARGA DAN KUALITAS PRODUK TERHADAP NIAT BELI ULANG PADA PRODUK LOKAL SCARLET WHITENING - Anggun Azizah; Kussudyarsana Kussudyarsana (POLITEKNIK LP3I JAKARTA, 2025)
In an era of increasing business competition, especially in the beauty industry, effective marketing strategies are key in building consumer loyalty. Local products such as Scarlet Whitening are required to not only attract new consumers, but also retain existing customers through repeat purchases. Factors such as the use of celebrity endorsers, competitive pricing, and product quality are important aspects that influence consumer decisions to make repeat purchases. This study aims to analyze Celebrity Endorser, Price and Product Quality on Repurchase Intention on Scarlet Whitening local products. This research method is quantitative. The population in this study were all Muhammadiyah Surakarta students. The number of samples in this study were 185 respondents. The sampling technique in this study used a purposive sampling method. The data source of this research is primary data. This study used a questionnaire to collect data. The data collected for this study were analyzed using the Partial Least Square (PLS) program. The results of this study are celebrity endorsement has a positive and significant effect on repurchase intentions. Price has no positive and insignificant effect on repurchase intention. Product quality has a positive and significant effect on repurchase intention.